China-Pakistani economic corridor project bring the international trade, healthcare, self-efficacy, and social performance facility to Gilgit city, Pakistan. Issue 9 (September 2022) - Naz, Shakela; Yeyan, Wu; Zhe, Liu; Ren, Keyao; Wenjie, Yu
Abstract: This paper aims to identify the impact of China-Pakistani economic corridor project bring the international trade, healthcare, self-efficacy, and social performance facility to Gilgit city, Pakistan. A questionnaire survey was carried out on the scholar presently studying at different universities in china. The 50% scholar estimation silk road enhanced, and 11% have no idea about the increasing of the healthcare opportunity in Gilgit. The 83% scholar estimation silk road improved Gilgit infrastructure. The 66% scholar estimated yes, 10% no, and 50% have no idea about the silk road brings peace and stability to Gilgit. The majority of respondents in the survey had a positive approach to the China–Pakistan Silk Road (CPSR). The results of the analysis show a better knowledge of the communication between the project and social media. This study will help china intensify its products to the middle east, africa, and europe. The (CPSR) is believed to create a shift in china's economic and political position in the world. in addition to strengthening the time-tested economic partnership between the two countries, the CPSR is expected to transform china's economic and political situation in the world. Abstract : Gilgit city; History of CPSR; Healthcare; International trade; Social performance.